Penegakan Hukum Lingkungan Hidup Melalui Gugatan Perbuatan Melawan Hukum - Luqman Hakim (CV Rewang Rencang, 2021)
Environmental damage has a negative impact on the lives of living creatures around it, especially humans. Environmental law enforcement can be carried out with a lawsuit against the law (PMH) in the District Court in accordance with the PPLH Law, where the Defendant can be sentenced to carry out a decision to pay material or immaterial compensation and carry out environmental management. The PPLH Law provides space for victims of environmental damage to defend their rights and demands the preservation of the environment damaged by industrialization. The PMH lawsuit as referred to in Article 1365 of the Civil Code must prove all elements in it, except for the element of error that does not need to be proven or ruled out, because, in environmental law, industrial players are charged with absolute liability (Strict Liability).